THE DEVELOPMENT OF STATE AID FOR THE PURPOSES OF REGIONAL DEVELOPMENT AND SUPPORT OF SMALL AND MEDIUM-SIZED ENTERPRISES - ANDRUKHOVYCH, Dana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the process of development of regional state aid as a tool of state regulation of disparities in regional development and support of depressed regions in such excessively difficult conditions as war. State aid is actively used as a tool of state regulation to equalize disparities in regional development and support depressed regions. In 2015-2020, decentralization was carried out in Ukraine - an administrative-territorial reform, because of which the administrative-territorial division changed, and local self-government bodies received greater powers to collect and allocate financial resources. This actualized the task of improving state aid based on the study and implementation of European rules for monitoring and providing regional state aid. The work uses data from scientific publications, expert assessments of international projects, and official sources of state authorities for a comprehensive analysis of the development of regional state aid for small and medium-sized enterprises. It was established that the study of the regulatory regulation of the process of providing regional state aid in the EU revealed certain problems related to ensuring its effectiveness as a tool for supporting balanced regional economic development on the basis of maintaining effective competition between regions by targeting the goal of attracting additional private investments in unstable ( underdeveloped) regions. The analysis of the European practice of providing regional state aid showed the existence of dilemmas in this area, which to some extent are solved by implementing the rule, when in regions with a low level of development, state aid is provided for the implementation of investment projects, and in regions with a high level of development - only for SMEs. In our opinion, the decentralization reform had positive results for the financial strength of territorial communities. With the expansion of their financial capabilities, the task of focusing their attention on the analysis and systematization of decisions regarding the allocation of state aid for timely notification to the AMCU became more relevant. The conclusions emphasize the importance of the development process and the provision of state aid should be aimed at promoting the development of Ukrainian business, first of all, SMEs, at their adaptation to the needs of the wartime economy, expanding financing of SMEs of all segments in the form of credit and grant programs.